CHARACTERISTICS OF YOUTH CIVIC ENGAGEMENT IN LIEPAJA CITY - Jurs, Pāvels; Samuseviča, Alīda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Youth civic engagement is an essential precondition for the preservation of democratic values and the existence of civil society. The implementation of the competence approach in the education process in Latvia provides as one of the key priorities of pedagogical work – encourage students' civic engagement and personal responsibility, developing students' thinking and self-initiative, the skills to be accountable to the citizens of society with the development national, historical and civic consciousness and understanding of social processes, as well as to promote their social activity and persistent habits in dealing with their peers to share solving multi-level problems related to the future of the local community and sustainable development. The aim of the research is: on the bases of theoretical research of civic problems and the analysis of the results of the carried out survey (quantitative data processing), to identify expressions of civic engagement of young people (from 9 to 12 grade students) in Liepaja (Latvia) focusing on different categories: (I) self-esteem of civic participation; (II) the willingness of young people to take responsibility; (III) self-realization of youth civic participation (IV) level of awareness among young people; (V) interaction of families and students in the context of the formation of a responsible position. The survey results reflect: relatively high self-esteem of civic engagement of students; low political engagement and political system scores; the untapped potential of young people in the context of civic engagement at school and city level.